Localized multidrug co-delivery by injectable self-crosslinking hydrogel for synergistic combinational chemotherapy. Issue 25 (7th June 2017) - He, Mengmeng; Sui, Junhui; Chen, Yafang; Bian, Shaoquan; Cui, Yani; Zhou, Changchun; Sun, Yong; Liang, Jie; Fan, Yujiang; Zhang, Xingdong
Abstract : The multidrug co-loaded injectable hydrogels against tumor showed superiority and potential application values. Abstract : Significant progress has been made in the use of injectable hydrogels as drug carrier systems to treat cancers by the peritumoral-localized co-delivery of multiple drugs with different therapeutic mechanisms. In this study, a novel, injectable self-crosslinking HA–SH hydrogel was able to concurrently encapsulate multiple drugs (sorafenib, doxorubicin, and metformin) to enhance chemotherapy efficacy. The hydrogel was relatively stable under physiological conditions and could quickly and directly release the loaded drugs to the tumor site in a reductive tumor microenvironment. The in vitro antitumor activity and cell-apoptosis assay demonstrated that the hydrogel loaded with multiple drugs (Gel + DS or Gel + DSM) showed obvious synergistic effects against breast cancer cells. The combinational chemotherapy enhanced the sensitivities of tumor cells and promoted tumor cell apoptosis after peritumoral administration. Compared with the single drug-loaded hydrogel, the hydrogel co-loaded with multiple drugs (Gel + DSM) showed the best tumor growth inhibition. Moreover, the monitoring of mice weight and ex vivo histological analysis of the main organs indicated that localized treatment with the hydrogel co-loaded with multiple drugs (Gel + DSM) obviously relieved the systemic toxicity and showed promise for inhibiting tumor metastasis, suggesting the superiority and potential application prospects of the injectable, self-crosslinking hydrogel co-loaded with multiple drugs.